STUDY LITERATURE REVIEW: STUDENT LEARNING OUTCOMES IN MATHEMATICS LEARNING WITH PROBING PROMPTING MODEL - Zahria, Dian Nissa (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to analyze student learning outcomes in mathematics learning using the probing prompting model. The probing prompting learning model involves providing a series of questions that guide and test students' thinking, to improve the thinking process that links previous knowledge and experience with the newly learned material. This research is a literature research or literature review study. Data collection was done by searching for scientific articles relevant to the topic. The data obtained is secondary data in the form of scientific articles and research journals. The information obtained is reduced and then described scientifically to arrive at a research result. From the review of several studies that have applied the probing prompting model to mathematics learning, it can be concluded that the application of the probing prompting model has a positive impact on students' mathematics learning outcomes.